The Influence of Broken Home Family on the Socialization Process of Children - Latifah Zahra Ai’ni; Yarhamna Yarhamna; Zulharfi Zulharfi (State Institute of Islamic Studies Batusangkar, 2023)
The significant number of divorce cases, including both divorces and widowhoods, in Indonesia, particularly in the West Sumatra region, known colloquially as 'Broken Homes,' has raised concerns among researchers regarding its potential influence on the socialization process of children. This research was conducted using a descriptive method with a qualitative approach, making it a mini research study. The data collection technique employed was online interviews conducted through Google Forms. The study subjects were children who had experienced a broken home and were residing in the West Sumatra area. The research results revealed that the concept of a Broken Home family can indeed impact the socialization process of children, encompassing primary socialization aspects such as shifts in a child's personality, education, and habits, as well as secondary socialization processes involving mass media, formal institutions, and the immediate environment. These changes were found to be influenced by both parties involved—namely, children and families—with remaining motivation, strong religious knowledge, and mutual support serving as contributing factorsAbstract:The significant number of divorce cases, including both divorces and widowhoods, in Indonesia, particularly in the West Sumatra region, known colloquially as 'Broken Homes,' has raised concerns among researchers regarding its potential influence on the socialization process of children. This research was conducted using a descriptive method with a qualitative approach, making it a mini research study. The data collection technique employed was online interviews conducted through Google Forms. The study subjects were children who had experienced a broken home and were residing in the West Sumatra area. The research results revealed that the concept of a Broken Home family can indeed impact the socialization process of children, encompassing primary socialization aspects such as shifts in a child's personality, education, and habits, as well as secondary socialization processes involving mass media, formal institutions, and the immediate environment. These changes were found to be influenced by both parties involved—namely, children and families—with remaining motivation, strong religious knowledge, and mutual support serving as contributing factors.